Management of plant-parasitic nematodes in spice crops - Manimaran, B; Sellaperumal, C (Indian Horticulture, 2025)
India’s spice sector, spread over 4.31 million ha, faces significant yield losses due to plant-parasitic nematodes (PPNs) such as Radopholus similis, Meloidogyne spp., Pratylenchus spp., and Rotylenchulus reniformis. These nematodes impair root systems, reduce nutrient uptake, and promote secondary infections, causing yield losses of 29–64% in key crops like black pepper, turmeric, ginger, and cardamom. This Paper highlights the major nematode pests affecting spice crops, their damage symptoms, and the resulting disease complexes. Effective management of PPNs requires an integrated approach combining preventive, cultural, biological, physical, and chemical strategies. Adoption of Integrated Nematode Management (INM) practices is essential to ensure sustainable production, export quality, and long-term resilience in India’s spice cultivation systems.